Migraine as a risk factor associated with hypertensive disorders of pregnancy - Serva, Gabriel Braga Diégues; Guerra, Leonardo Santos Calvacanti; Serva, Vilneide Maria Santos Braga Diégues; Serva, Waldmiro Antônio Diégues; Belo, Marcela Patrícia Macêdo; Valença, Marcelo Moraes; Caminha, Maria de Fátima Costa (Headache Medicine, 2014)
Objectives: To identify if the presence of migraine before pregnancy predisposes to hypertensive disorders of pregnancy. Methods: Observational study undertaken from a database of a follow-up study, composed of women consecutively assisted, at the first postnatal week, at IMIP. Its objective was to evaluate the course of migraine during pregnancy and postpartum in women with migraine before pregnancy. The Fisher exact test was used considering the significance level of less than 5%. Results: Of the 686 women, 38.8% were migraine sufferers before pregnancy. 14.3% referred hypertensive disorders of pregnancy. The presence of migraine before pregnancy and to have been submitted to a cesarean section (p<0.001) were factors associated with the presence of hypertensive disorders in pregnancy. Conclusion: Migraine before pregnancy is an associated factor to hypertensive disorders of pregnancy. The diagnosis of migraine should always be taken into consideration during antenatal care, for the prevention of complications.